2006
DOI: 10.1115/1.2221327
|View full text |Cite
|
Sign up to set email alerts
|

Rotordynamic Force Coefficients of Pocket Damper Seals

Abstract: This paper presents measured frequency dependent stiffness and damping coefficients for 12-bladed and 8-bladed pocket damper seals (PDS) subdivided into four different seal configurations. Rotating experimental tests are presented for inlet pressures at 69 bar (1000 psi), a frequency excitation range of 20–300 Hz, and rotor speeds up to 20,200 rpm. The testing method used to determine direct and cross-coupled force coefficients was the mechanical impedance method, which required the measurement of external sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…It is important to note that past CFD methods for labyrinth seal and hole-pattern seal only computed four rotordynamic coefficients with the fact that labyrinth seal and holepattern seal have the same direct force coefficients and opposite sign equal magnitude cross coupling force coefficients in the orthogonal direction (x and y). However, in some cases, the PDS have the same-sign unequal-magnitude cross coupling stiffness and damping, such as the diverging configurations of six-bladed, eight-bladed and twelve-bladed PDS [8]. Therefore, these CFD methods are not suitable for computations of a full set of rotordynamic coefficients of the PDS.…”
Section: Introductionmentioning
confidence: 95%
“…It is important to note that past CFD methods for labyrinth seal and hole-pattern seal only computed four rotordynamic coefficients with the fact that labyrinth seal and holepattern seal have the same direct force coefficients and opposite sign equal magnitude cross coupling force coefficients in the orthogonal direction (x and y). However, in some cases, the PDS have the same-sign unequal-magnitude cross coupling stiffness and damping, such as the diverging configurations of six-bladed, eight-bladed and twelve-bladed PDS [8]. Therefore, these CFD methods are not suitable for computations of a full set of rotordynamic coefficients of the PDS.…”
Section: Introductionmentioning
confidence: 95%
“…Liu and Wang [9] found that the seal force could further deform the flexible rotor as well as reduce the first critical speed and destabilization rotating speed of the rotor. Ertas [10] applied the dynamic pressure-response method to determine the frequency-dependent force coefficients of pocket damper seals. The frequencydomain method can be applied through excitation experiments to obtain the rotordynamic characteristics; it is increasingly adopted by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The frequencydomain method can be applied through excitation experiments to obtain the rotordynamic characteristics; it is increasingly adopted by researchers. Childs and his teams [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] conducted productive research on different seals, such as the labyrinth seal, smooth annular seal, hole pattern stator annular seal, honeycomb seal, and pocket seal, among others. Many factors have been considered and tested in several rigs, such as eccentricity ratio, pre-rotation, pressure ratio, seal type, speed, clearance, excitation frequency, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the subject-matter literature a simplification which consists in neglecting the inertia coeffcients in the model, can be found [5,6] …”
Section: Pressure Forces -Linear Modelmentioning
confidence: 99%
“…Mutual relationship between pressure force and displacement of rotor against casing is usually described by means of the so called "seal dynamic coeffcients" [1][2][3][4][5][6][7][8][12][13][14] which can be incorporated into whole model of turbine set during its designing process. Three kinds of the dynamic coefficients can be distinguished: stiffness, damping nad inertia ones.…”
Section: Pressure Forces -Linear Modelmentioning
confidence: 99%